Towns and Villages of the Lower Ohio - Bigham, Darrel E. (Book collections on Project MUSE., 1998)
America. Enterprise. Metropolis. Cairo. Rome. These are a few of the grandly named villages and towns along the lower Ohio River. The optimism with which early settlers named these towns reveals much about the history of American expansion. Though none became the next great American city, it was not for lack of ambition or entrepreneurial spirit. Why didn't a major city develop on the lower Ohio? What geographic, economic, and cultural factors caused one place to prosper and another to wither? How did Evansville become the largest and most influential city in the region? How did smaller cities.